Keterkaitan Manusia, Ruang Dan Kebudayaan - H.R. Bintarto (Balai Arkeologi Yogyakarta, 1995)
The dimensions of space and time are very meaningful for archaeological research, because the continuity of archaeology goes through a time process that is domiciled in a certain area or area on earth. This archaeological diffusion occurs over a considerable period of time and through varied geographical conditions. Therefore, the study of space in archeology covers various aspects of human life in the past, both in terms of socio-cultural, socio-economic as well as from an eco-technological perspective.